Hadith commentary repository: an ontological approach - Jaafar, Amir Hamzah; Che Pa, Noraini (School of Computing, UUM College of Arts and Sciences, 2017)
Hadith Commentary are the description of a particular hadith by a scholar and its relations to other parts of the Holy Scriptures including other variations of hadith that has narrated by a different narrator with a different matn. Without it, the lateral meaning of the matn can be understood out to the original scope and could result in an incorrect interpretation. In-formation on hadiths on the web are scattered and not organized and usually is embedded in text and writing. This information will be hard to analyze and extracted to be kept and referenced. There are applications, websites and portals that provide online information and functionalities related to hadith which includes hadith search, isnad search, term search, hadith classification, narration view and translation. However, all these hadith websites are without any accompanying commentary that will help a common Muslim or the general public to understand and put the hadith into context, thus this situation can result in a misinterpretation of the hadith that leads to the misconception of the deen. We presented the development process of the Hadith Commentary Ontology and tested the ontology against the purpose of the ontology (The ability of the ontology to produce result or answer the requirement questions). The main contribution of this research is that the ontology can support the storage of Hadith Commentary which is not currently available and we foresee that with the availability of the hadith commentary ontology will further help ontological based repositories to integrate and provide a base for an online hadith corpus and linkages among Islamic related ontologies.